Why do smart people make such stupid mistakes? : a practical negotiation guide to more profitable client relationships for marketing and communication agencies, sales teams and professional service people /: a practical negotiation guide to more profitable client relationships for marketing and communication agencies, sales teams and professional service people. (2011) - Merrington, Chris
No abstract available